2014
DOI: 10.1038/bjc.2014.457
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester stimulates ethanolamine release from the metastatic basal prostate cancer cell line PC3 but not from prostate epithelial cell lines LNCaP and P4E6

Abstract: Background:Malignancy alters cellular complex lipid metabolism and membrane lipid composition and turnover. Here, we investigated whether tumorigenesis in cancer-derived prostate epithelial cell lines influences protein kinase C-linked turnover of ethanolamine phosphoglycerides (EtnPGs) and alters the pattern of ethanolamine (Etn) metabolites released to the medium.Methods:Prostate epithelial cell lines P4E6, LNCaP and PC3 were models of prostate cancer (PCa). PNT2C2 and PNT1A were models of benign prostate ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 102 publications
1
10
0
Order By: Relevance
“…Thus, given that the TAT is known to be a short cell-penetrating peptide, we suspect an additional, intracellular mechanism to explain the increased anticancer properties of tMP-C. This in line with reports that mastoparan can interact with the phospholipid phase of the mitochondrial membrane, which has been implicated as the leading cause for inducing apoptosis in B16F10-Nex2 melanoma cells 38 , 53 , and can selectively activate phospholipase or inhibit ATPase activity to cause failure in cell proliferation and metabolism 54 , 55 . The addition of the TAT peptide to MP-C would presumably increase access to such intracellular targets to induce apoptotic cell death 56 , 57 while leaving the outer cell membrane more intact in comparison to the native peptide.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, given that the TAT is known to be a short cell-penetrating peptide, we suspect an additional, intracellular mechanism to explain the increased anticancer properties of tMP-C. This in line with reports that mastoparan can interact with the phospholipid phase of the mitochondrial membrane, which has been implicated as the leading cause for inducing apoptosis in B16F10-Nex2 melanoma cells 38 , 53 , and can selectively activate phospholipase or inhibit ATPase activity to cause failure in cell proliferation and metabolism 54 , 55 . The addition of the TAT peptide to MP-C would presumably increase access to such intracellular targets to induce apoptotic cell death 56 , 57 while leaving the outer cell membrane more intact in comparison to the native peptide.…”
Section: Discussionsupporting
confidence: 79%
“…The source for ethanolamine detected in urine has not been established. Cell lines in vitro release ethanolamine into culture medium from cell membrane turnover (59). Within the gastrointestinal tract, available ethanolamine is assumed to derive from the breakdown of phospholipid from the turnover of the epithelium and dietary phospholipid (60).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of the log2-ratios of significantly (p ≤ 0.05) up-regulated metabolites for the three treatment groups revealed, that ethanolamine was synergistically up-regulated after combined exposure to genistein and calcitriol ( Fig 5 ). Schmitt et al [ 27 ] just recently showed that the antitumor agent phorbol-ester stimulates release of ethanolamine from the metastatic basal prostate cancer cell line PC3 suggesting that elevated ethanolamine production could be associated with antitumor activity.…”
Section: Discussionmentioning
confidence: 99%